m6A modification: recent advances, anticancer targeted drug discovery and beyond - Deng, Li-Juan; Deng, Wei-Qing; Fan, Shu-Ran; Chen, Min-Feng; Qi, Ming; Lyu, Wen-Yu; Qi, Qi; Tiwari, Amit K.; Chen, Jia-Xu; Zhang, Dong-Mei; Chen, Zhe-Sheng (Molecular cancer, 2022)
Abnormal N6-methyladenosine (m6A) modification is closely associated with the occurrence, development, progression and prognosis of cancer, and aberrant m6A regulators have been identified as novel anticancer drug targets. Both traditional medicine-related approaches and modern drug discovery platforms have been used in an attempt to develop m6A-targeted drugs. Here, we provide an update of the latest findings on m6A modification and the critical roles of m6A modification in cancer progression, and we summarize rational sources for the discovery of m6A-targeted anticancer agents from traditional medicines and computer-based chemosynthetic compounds. This review highlights the potential agents targeting m6A modification for cancer treatment and proposes the advantage of artificial intelligence (AI) in the discovery of m6A-targeting anticancer drugs. Graphical abstract Three stages of m6A-targeting anticancer drug discovery: traditional medicine-based natural products, modern chemical modification or synthesis, and artificial intelligence (AI)-assisted approaches for the future.